2018
DOI: 10.5430/ijhe.v7n6p1
|View full text |Cite
|
Sign up to set email alerts
|

Career Choice, Barriers, and Prospects of Asian American Social Workers

Abstract: The current study explored factors influencing career choices of Asian American social workers and assessed if their personal characteristics and career-related experiences affected their perceived glass ceiling, perception of ethnic discrimination, and perception of career prospects.  A total of 208 Asian American social work administrators, supervisors, practitioners and graduate social work students participated in a comprehensive online survey.  Participants provided basic demographic and career-related in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
0
2
0
1
Order By: Relevance
“…According to 2015 data reported by the Council of Social Work Education (CSWE, 2017), Asians represent 3.6% of active social workers; and although underrepresented in human and social service fields, reports indicate that the number of Asian American social workers have been growing steadily over the past decade (Salsberg et al, 2017). It is also worth mentioning that Asian American college students found that their interest in social work was strongly influenced by: (a) the congruence between their personal values and social work values (Lee, 2008;Kwong, 2018); and (b) their commitment to helping people with social problems as opposed to desires of becoming a therapist or the perceived prestige of the profession (Lew, 2005). These examples underscore Asian American's recognition of the social, health, and systemic challenges that uniquely impact historically marginalized groups and their intrinsic motivation for social change.…”
Section: Asian American Social Workersmentioning
confidence: 99%
“…According to 2015 data reported by the Council of Social Work Education (CSWE, 2017), Asians represent 3.6% of active social workers; and although underrepresented in human and social service fields, reports indicate that the number of Asian American social workers have been growing steadily over the past decade (Salsberg et al, 2017). It is also worth mentioning that Asian American college students found that their interest in social work was strongly influenced by: (a) the congruence between their personal values and social work values (Lee, 2008;Kwong, 2018); and (b) their commitment to helping people with social problems as opposed to desires of becoming a therapist or the perceived prestige of the profession (Lew, 2005). These examples underscore Asian American's recognition of the social, health, and systemic challenges that uniquely impact historically marginalized groups and their intrinsic motivation for social change.…”
Section: Asian American Social Workersmentioning
confidence: 99%
“…Sono stati elaborati anche strumenti per rilevare motivazioni e interessi specifici sottostanti alla scelta dei percorsi in ambito psicologico (Anja & Diseth, 2020) o alla scelta delle professioni sociali (Kwong, 2018).…”
Section: Validità DI Criteriounclassified
“…To address gender disparities, there is a greater need for preparedness for younger women, owing to societal and community influences (Kwong, 2018;Paris and Decker, 2016). However, some studies in the past on perceived barriers have proposed that challenges in professional and occupational attainment may be negatively anticipated by marginalized groups (Ó N araigh, 2020).…”
Section: Literature Review 21 Career Development and Preparednessmentioning
confidence: 99%